2019
DOI: 10.18261/issn.2535-2512-2019-06-05
|View full text |Cite
|
Sign up to set email alerts
|

Rusproblem og endring i eit diskursperspektiv: Ein analyse av praksisforteljingar

Abstract: Rusproblem er eit fleirtydig fenomen der ulike forståingar har dominert gjennom historia og mellom samfunn. Også i vår samtid blir samfunnets reaksjonar mot problematisk rusbruk utforma i skjeringspunkt mellom ulike ideologiar og forståingar. Kva faglege, ideologiske og moralske forståingar som rår, dannar vilkår for korleis hjelp til personar med rusproblem kan utformast. Éi forståing som i vår samtid har fått auka støtte i den internasjonale forskingslitteraturen, er at rusproblem er ei langvarig liding preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…They emphasise that learning processes must occur in interaction and collaboration with fellow patients and staff [ 13 ]. Other practice studies show that language, culture, and discursive processes are essential in determining how patients are understood [ 14 ]. It takes time for substance users to change their perceptions from being addicted to substances to becoming participants in society [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…They emphasise that learning processes must occur in interaction and collaboration with fellow patients and staff [ 13 ]. Other practice studies show that language, culture, and discursive processes are essential in determining how patients are understood [ 14 ]. It takes time for substance users to change their perceptions from being addicted to substances to becoming participants in society [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that the services had the same focus; they also offered services primarily to the individual who had the problem and not the entire family. Several earlier studies (Adams, 2008;Copello et al, 2010;Selseng & Ulvik, 2019) support this finding and have reported how the dominant trends in substance-use policy favor an individual-oriented perspective that provides limited opportunities for integrated work with families.…”
Section: Discussionmentioning
confidence: 64%
“…In this article, we do not distinguish between the use of legal substances, such as alcohol, and the use of illegal drugs, insofar as our focus is on how families are living with consequences that may result from all types of substance-use problems. It is commonly understood that PSU has many of the characteristics of a chronic condition; PSU is, for instance, marked by cycles of recovery, ongoing use, and repeated treatments (Fleury et al, 2016;McKay, 2017;McLellan et al, 2000;Selseng & Ulvik, 2019;Sheedy & Whitter, 2013). There is a high and long-lasting risk for repetitive episodes of substance use.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore essential that professionals have this understanding of the family's long term-perspectives and the consequences for the siblings in particular, both while their siblings are still alive and after they have died. However, several earlier studies (Adams, 2008;Copello et al, 2010;Selseng & Ulvik, 2019) also reported how the dominant trends in substance-use policies provide limited opportunities to implement any integrated work with families. This study, on the other hand, clearly shows how important it is to offer families the opportunity to enter joint conversations so that they can receive the help and support they need for the ongoing challenges they are subjected to, and to prevent a breakdown of the family unit in the future.…”
Section: Concluding Comments and Implications For Practicementioning
confidence: 99%